Semiconductor and Circuit Modelling Methods for Next Generation RF Receiver Protection Devices - Matthews, Luke Jordan Kingsley (2025)
This thesis explores modelling a receiver protector system (RxP) in un precedented detail. Using the UTLM method and software developed at the University of Nottingham by Prof. Phil Sewell and Prof Ana Vukovic, the research presented in this thesis uses detailed simulations to initially explore the effects of adding some of the key components in a piecewise manner. Predictably, the inclusion of the inductive post has the most significant impact on the performance, with the diameter of the post varied and investigated, along with the diameter of the upper boss and lower cavity and the depth of protrusion for both the upper boss and lower cavity. Furthermore, a detailed analysis of the PiN diode model structure is presented. Progressing the model of the diode from a solid metallic block with simple behaviour, to a model of a silicon PiN diode where each of the 3 layers is defined individually, it is hoped that this final model can then be the foundations for further research into the semiconductors that drive RxP systems. Finally, an exploration into the scattering effects of the RxP system is presented. The inductive post has the capability of scattering the incident signal, some of which excite modes with higher cut-off frequencies. Which modes are excited and what criteria they most fulfil are also considered. The scattering into higher order modes presented in this research is an as yet unexplored area of study in electromagnetic simulation work. i The results presented here offer an insight into the behaviour of the RxP system above the desired operating band and indicate what happens to the “lost” power at higher frequencies. This research was impacted by the 2020 COVID-19 Pandemic, with restrictions in the UK limiting access to required infrastructure and reducing the collaboration opportunities with some stakeholders. Furthermore, as this research is based around modelling a practical system, commercial sensitivities have mean that some parameters have been modified and other elements remain unpublished to protect the IP of the industry ad visors. Nonetheless, the data presented in this thesis provides a detailed analysis of specific elements of the RxP, a detailed development of the PiN diode model and an interesting exploration of the scattering effects of the RxP at frequencies higher than the operating band, and how the response of the system at these frequencies is similar to that of a high-pass filter.